Bibliometric Analysis of Postgraduate Theses on the Relationship Between Communication and Tourism - Mahmut Barakazı; Gökhan Kuzucanlı (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
In this research, it is aimed to reveal the current situation and trends in the related subject by examining the master's and doctoral theses prepared in Turkey in the relationship between communication and tourism with the bibliometric analysis method. In this context, 34 postgraduate thesis studies, which are related to the subject and which were shared and accessed by the Higher Education Institution database between 1990-2022, were included in the research. The data obtained from the research were analyzed with the help of SPSS statistical analysis package program, and frequency and percentage analyzes of the data were made. In the light of research findings; It has been determined that the most postgraduate theses among universities were prepared within the body of 'Selçuk University'. In addition to this, it has been concluded that 'quantitative research' methods are mostly used as a method in the researches. It is understood that the terms 'Tourism', 'Communication' and 'Public Relations' come to the fore in the keywords used in graduate theses. With this research, by drawing attention to the concepts of tourism and communication within the framework of postgraduate research, suggestions are made to researchers and stakeholders to examine them in different dimensions.